Superconductivity Induced by Oxygen Doping in Y2O2Bi. Issue 34 (3rd April 2017) - Cheng, Xiyue; Gordon, Elijah E.; Whangbo, Myung‐Hwan; Deng, Shuiquan
Abstract: When doped with oxygen, the layered Y2 O2 Bi phase becomes a superconductor. This finding raises questions about the sites for doped oxygen, the mechanism of superconductivity, and practical guidelines for discovering new superconductors. We probed these questions in terms of first‐principles calculations for undoped and O‐doped Y2 O2 Bi. The preferred sites for doped O atoms are the centers of Bi4 squares in the Bi square net. Several Bi 6p x / y bands of Y2 O2 Bi are raised in energy by oxygen doping because the 2p x / y orbitals of the doped oxygen make antibonding possible with the 6p x / y orbitals of surrounding Bi atoms. Consequently, the condition necessary for the "flat/steep" band model for superconductivity is satisfied in O‐doped Y2 O2 Bi. Abstract : Ripples in the Dirac Sea : Density functional calculations reveal that the preferred sites for oxygen doping in Y2 O2 Bi are the centers of the Bi4 squares in bismuth nets. Oxygen doping of Y2 O2+δ Bi satisfies the conditions of the "flat/steep" band model for superconductivity.